*The purpose of this argument is to describe the reader.*

Premise 1: I am Alive.

(∃z)(A(z))

Definition 1: It is false that something is Alive and not Conscious.

(∀x)(A(x)>C(x))

Definition 2: It is false that something is Conscious and not a Mind.

(∀x)(C(x)>M(x))

Definition 3: All Knowledge is a subset of Awareness.

(∀x)((x∈K)>(x∈W))

Definition 4: Awareness is a subset of the Mind.

(∀x)((x∈W)>(x∈M))

Premise 2: Observable reality is a subset of the Mind.

(OR⊆M)

Premise 3: The Mind creates observable reality.

(M)BA(OR)

Premise 4: The Mind derives objective morality.

(M⊢(OM))

Definition 5: If all knowledge is a subset of any Mind, then said Mind is omniscient.

(∀M)[(K⊆M)>SC(M)]

Definition 6: Everything that observable reality is a subset of is omnipresent.

(∀Q)[(OR⊆Q)>PR(Q)]

Definition 7: Everything that creates observable reality is omnipotent.

(∀Q)[(Q)BA(OR)>PO(Q)]

Definition 8: Everything that derives objective morality is omnibenevolent.

(∀Q)[(Q⊢(OM))>BE(Q)]

Definition 9: Everything: omniscient, omnipresent, omnipotent and omnibenevolent is God.

(∀Q)[(SC(Q)&PR(Q)&PO(Q)&BE(Q))>G(Q)]

Axiom: For all x, Q, and P, if x is a Q and Q is a P, then x is a P.

∀(x, Q, P)[(Q(x)&P(Q))>P(x)]

Conclusion: I AM God. (Proof 3)

(∃z)(Gz)

I think, therefore let there be light.

I am the Way, the Truth, and the Life.

Divine revelation is self-actualization.

We are made in God’s image.

Thanks for playing!

Translation Schema:

(z = I);(A = Alive);(C = Conscious);(M = The Mind);(K = Knowledge);(W = Awareness);

(OR = Observable Reality);(BA = Brought About);(OM = Objective Morality);(G = God);

(SC = Omniscient);(PR = Omnipresent);(PO = Omnipotent);(BE = Omnibenevolent)

Proof:

Premise 1: (∃z)(A(z))

Premise 2: (∀x)(A(x)>C(x))

Premise 3: (∀x)(C(x)>M(x))

Premise 4: (∀x)((x∈K)>(x∈W))

Premise 5: (∀x)((x∈W)>(x∈M))

Premise 6: (OR⊆M)

Premise 7: (M)BA(OR)

Premise 8: (M⊢(OM))

Premise 9: (∀M)[(K⊆M)>SC(M)]

Premise 10: (∀Q)[(OR⊆Q)>PR(Q)]

Premise 11: (∀Q)[(Q)BA(OR)>PO(Q)]

Premise 12: (∀Q)[(Q⊢(OM))>BE(Q)]

Premise 13: (∀Q)[(SC(Q)&PR(Q)&PO(Q)&BE(Q))>G(Q)]

Premise 14: ∀(x, Q, P)[(Q(x)&P(Q))>P(x)]

Deduction 1 (Existential Instantiation, P1): A(a)

Deduction 2 (Universal Instantiation, P2): A(a)>C(a)

Deduction 3 (Universal Instantiation, P3): C(a)>M(a)

Deduction 4 (Hypothetical Syllogism, D2, D3): A(a)>M(a)

Deduction 5 (Modus Ponens, D1, D4): M(a)

Deduction 6 (Universal Instantiation, P4): (z∈K)>(z∈W)

Deduction 7 (Universal Instantiation, P5): (z∈W)>(z∈M)

Deduction 9 (Hypothetical Syllogism, D6, D7): (z∈K)>(z∈M)

Deduction 10 (Universal Generalization, D9): (∀x)((x∈K)>(x∈M))

Deduction 11 (Definition of Subset, D10): K⊆M

Deduction 12 (Universal Instantiation, P9): (K⊆M)>SC(M)

Deduction 13 (Modus Ponens, D11, D12): SC(M)

Deduction 14 (Universal Instantiation, P10): (OR⊆M)>PR(M)

Deduction 15 (Modus Ponens, P6, D14): PR(M)

Deduction 16 (Universal Instantiation, P11): (M)BA(OR)>PO(M)

Deduction 17 (Modus Ponens, P7, D16): PO(M)

Deduction 18 (Universal Instantiation, P12): (M⊢(OM))>BE(M)

Deduction 19 (Modus Ponens, P8, D18): BE(M)

Deduction 20 (Conjunction, D13, D15): SC(M)&PR(M)

Deduction 21 (Conjunction, D17, D19): PO(M)&BE(M)

Deduction 22 (Conjunction, D20, D21): SC(M)&PR(M)&PO(M)&BE(M)

Deduction 23 (Universal Instantiation, P13): (SC(M)&PR(M)&PO(M)&BE(M))>G(M)

Deduction 24 (Modus Ponens, D22, D23): G(M)

Deduction 25 (Conjunction, D5, D24): M(a)&G(M)

Deduction 26 (Universal Instantiation, P14): (M(a)&G(M))>G(a)

Deduction 27 (Modus Ponens, 25, 26): G(a)

Deduction 28 (Existential Generalization, D27): (∃z)(Gz)

Conclusion: (∃z)(Gz)

Source:

medium.com/@jgeor058/the-ontological-argument-for-the-existence-of-you-b5f793d5c167